2010
DOI: 10.5978/islsm.19.101
|View full text |Cite
|
Sign up to set email alerts
|

Low Reactive Level Laser Therapy in the Treatment of Post Herpetic Neuralgia

Abstract: Post herpetic neuralgia (PHN) can be an extremely painful condition which in many cases proves resistant to all the accepted forms of treatment. It is frequently most severe in the elderly and may persist for years with no predictable course. Since 1980, we have been applying low reactive level laser therapy (LLLT) for patients with PHN. We report herein on the results of a retrospective study concerning those patients in whom LLLT has been applied for pain attenuation of PHN. One hundred and twenty-three pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…LLLT is effective for PHN in the acute and chronic phase and the results demonstrate a significant reduction in PHN pain intensity and other complaints therefore LLLT will appear to be a valuable method for treating PHN. 19 Sasaki et al, 16 demonstrated that among 123 patient treated by LLLT showed an overall total improvement of 60.16% and it was concluded that LLLT was effective for PHN for the acute and chronic phase, but LLLT was particularly effective for the acute onset patient whose onset before treatment was 6 months or less .Also, the current results were supported by Mukhtar et al, 14 who found the efficacy of laser therapy in treating PHN was successfully proven by a study conducted on 15 patients, where the sample was PHN patients who were refractory to various drugs for 1 month -1 year. The results of this study found that 11 of 15 patients who received laser therapy for 16 sessions in 8 weeks stated that they were pain free and the remaining 4 reported significant pain reduction (more than 50%).…”
Section: Discussionmentioning
confidence: 99%
“…LLLT is effective for PHN in the acute and chronic phase and the results demonstrate a significant reduction in PHN pain intensity and other complaints therefore LLLT will appear to be a valuable method for treating PHN. 19 Sasaki et al, 16 demonstrated that among 123 patient treated by LLLT showed an overall total improvement of 60.16% and it was concluded that LLLT was effective for PHN for the acute and chronic phase, but LLLT was particularly effective for the acute onset patient whose onset before treatment was 6 months or less .Also, the current results were supported by Mukhtar et al, 14 who found the efficacy of laser therapy in treating PHN was successfully proven by a study conducted on 15 patients, where the sample was PHN patients who were refractory to various drugs for 1 month -1 year. The results of this study found that 11 of 15 patients who received laser therapy for 16 sessions in 8 weeks stated that they were pain free and the remaining 4 reported significant pain reduction (more than 50%).…”
Section: Discussionmentioning
confidence: 99%
“…Na NPHT a TLBI, é empregada para a diminuição da dor e para o reparo tecidual e neuronal. A redução da sintomatologia dolorosa é observada em vários estudos que utilizaram a TLBI para o tratamento da NPHT (SASAKI et al, 2010;MAAN et al, 1999;MOORE et al, 1988). Na reparação neuronal, Falaki, Nejat e Dalirsani (2014) afirmam que a TLBI estimula a produção de mielina, promovendo o aumento da função nervosa.…”
Section: Discussionunclassified